2013
DOI: 10.4161/onci.24524
|View full text |Cite
|
Sign up to set email alerts
|

A co-stimulatory trap set by myeloid leukemia cells

Abstract: The straightforward notion that tumor cells always exert immunosuppressive functions has been contradicted by the finding that myeloid leukemia cells can express potent co-stimulatory molecules. Indeed, the co-stimulatory support offered by leukemia cells can provoke helper T-cell responses. Unfavorably, this interaction allows leukemia cells to acquire immunosuppressive capacities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Inhibitors of PD-1 (nivolumab) and CTLA-4 (ipilimumab) have shown promise for the treatment of advanced melanoma and relapsed Hodgkin's lymphoma with response rates ranging from 7 to 40% [ 4–6 ]. In vitro studies have shown that acute myeloid leukemia (AML) may utilize the PD-1/PD-L1 axis to evade an anticancer immune response [ 7–10 ]. These findings have prompted development of clinical trials utilizing checkpoint inhibitors for adult malignancies.…”
mentioning
confidence: 99%
“…Inhibitors of PD-1 (nivolumab) and CTLA-4 (ipilimumab) have shown promise for the treatment of advanced melanoma and relapsed Hodgkin's lymphoma with response rates ranging from 7 to 40% [ 4–6 ]. In vitro studies have shown that acute myeloid leukemia (AML) may utilize the PD-1/PD-L1 axis to evade an anticancer immune response [ 7–10 ]. These findings have prompted development of clinical trials utilizing checkpoint inhibitors for adult malignancies.…”
mentioning
confidence: 99%